Adversity, social support and risk of self-harm during the COVID-19 pandemic. Issue 4 (25th July 2022) - Borschmann, Rohan; Moran, Paul A.
Summary: Little is known about the degree to which social factors interact with COVID-19-related adversity to increase the risk of self-harm thoughts and behaviours. Using data derived from a UK cohort study, Paul & Fancourt found that loneliness was associated with an increase in the odds of self-harm thoughts and behaviours, whereas high-quality social support protected against self-harm thoughts and behaviours. The authors concluded that it is the quality of social support and interactions, rather than the act of engaging in social interaction per se, that protects against self-harm in the context of adversity. The COVID-19 pandemic may exert longer-lasting effects on population mental health, and continued surveillance of mental health, including self-harm status, will be essential. If accompanied by appropriate measures of the availability and quality of social support, such monitoring could also inform the development of more effective adaptive interventions for those at risk of engaging in self-harm.